Hemostasis using a covered self‐expandable metal stent for pseudoaneurysm bleeding from the perihilar bile duct. Issue 1 (30th June 2022) - Ishii, Yu; Nakayama, Akihiro; Kikuchi, Kazuo; Nakatani, Kei; Konda, Kenichi; Mori, Daichi; Nishihara, Shigetoshi; Oikawa, Shu; Nomoto, Tomohiro; Usami, Tomono; Noguchi, Toshihiro; Mitsui, Yuta; et al.
Abstract: Although there are many reports of hemostasis with covered self‐expandable metal stent (CSEMS) for bleeding from the papilla of Vater and the intrapapillary and distal bile duct, there are rare reports of its use for hemostasis in the perihilar bile duct. We report the case of a patient undergoing supportive care for perihilar cholangiocarcinoma with acute cholecystitis after side‐by‐side placement of uncovered SEMS for perihilar bile duct obstruction. Percutaneous transhepatic gallbladder aspiration was performed upon admission, and hematemesis occurred the next day. Since computed tomography scanning showed a pseudoaneurysm in the right uncovered SEMS, hemostasis by interventional radiology (IVR) was performed thrice for massive bleeding; however, hemostasis could not be achieved. When endoscopic retrograde cholangiopancreatography was performed for scrutiny and treatment of melena and increased hepatobiliary enzyme, the endoscopic visual field could not be secured by bleeding, and changes in hemodynamics were observed; thus, IVR was required, but it was difficult to perform. Since bleeding from the right bile duct was expected, hemostasis was performed using CSEMS. This is the first report of hemostasis performed by placing a covered SEMS for bleeding from a pseudoaneurysm of the intrahepatic bile duct.